“Pharmacy for the pharmacist” or for the patient? On different trajectories of regulation on pharmacy markets across the CEE region - Szyszkowska, Emilia (Wydawnictwo Uniwersytetu Wrocławskiego, 2023)
The landscape of the pharmacy market across the Central Eastern Europe (CEE) region has changed significantly in the past few years. Some countries have decided to liberalize their regulations regarding the shape and size of the pharmacy market (such as Romania and Slovakia), while others have decided to seriously tighten the restrictions and introduce quantitative, ownership, demographic or geographical restrictions according to the “pharmacy for the pharmacist” rule (Poland, Hungary and the Baltic states). The paper presents different models of regulation that shape the pharmacy market across selected countries of the region. Based on desk research and a qualitative survey among representatives of pharmacy chains in the countries in question, the article also explores the issue of the impact of regulations restricting the development of the pharmacy market on the development of new pro-patient pharmacy services. Findings indicate that despite the COVID-19 pandemic having had a significant impact on new pharmacy services development almost everywhere, their inclusion into healthcare systems is easier and wider in countries with less restrictive market regulations.
Keywords: pharmacies; pharmacy market; regulations; market restrictions; deregulation; new pharmacy services; CEE